Estimated the Seasonal Change of Temperature in Iraq Using GIS Techniques - Abdul-Kareem, Asraa; Al-Timim, Amani; Al-Jumaily, Kais (Iraqi Journal of Science, 2024)
Global warming is the scientific evidence that air temperatures the near surface of Earth are rising, and that higher temperatures threaten dangerous consequences earth such as drought, disease, floods, lost ecosystems. This aim of this research is analyzed the monthly means of daily values of air temperature in Iraq for the period of 1979 to 2010 by using GIS techniques. Data were obtained from the European Center for Medium-range Weather Forecasts (ECMWF). The initial diagnosis showed that there is no significant increase of maximum values of the mean temperature for the four parts( northern, central, western, and southern ) of Iraq for the four seasons so we compared the area of maximum value of mean temperature which covered it and the results show there were an increase in the central and southern part of the country during summer and winter and there were no significant change in the temperature pattern for the northern and western part of the country , while the trend of change of the area of maximum value of mean temperature for spring and autumn and for the three periods were oscillating.